2019
DOI: 10.1111/codi.14747
|View full text |Cite
|
Sign up to set email alerts
|

Colectomy for caecal and sigmoid volvulus: a national analysis of outcomes and risk factors for postoperative complications

Abstract: Aim Colonic volvulus is a common entity encountered by colorectal surgeons, but there are few reports of national data regarding postoperative outcomes. The aim of this study was to describe the volvulus population, 30‐day outcomes following right‐ and left‐sided colectomy and risk factors for postoperative complications. Method The American College of Surgeons National Surgical Quality Improvement Program Database from 2012 to 2015 was utilized to identify patients with the diagnosis of ‘volvulus’ who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 11 publications
(16 reference statements)
2
29
1
Order By: Relevance
“…Second, compared with my own series [3], the postoperative morbidity rate (46.4%) is similar; Althans et al [1] give an acceptable mortality rate (3.4%) in SV patients treated with colectomy and primary anastomosis, despite a high incidence of seriously ill patients (ASA score ≥ 4, 16.3%). After propensity score matching, Dolejs et al [8] reported a 10.8% mortality rate in 232 SV patients treated with emergency colectomy and primary anastomosis in the same period (between 2012 and 2015) by using the same database (American College of Surgeons National Surgical Quality Improvement Program).…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…Second, compared with my own series [3], the postoperative morbidity rate (46.4%) is similar; Althans et al [1] give an acceptable mortality rate (3.4%) in SV patients treated with colectomy and primary anastomosis, despite a high incidence of seriously ill patients (ASA score ≥ 4, 16.3%). After propensity score matching, Dolejs et al [8] reported a 10.8% mortality rate in 232 SV patients treated with emergency colectomy and primary anastomosis in the same period (between 2012 and 2015) by using the same database (American College of Surgeons National Surgical Quality Improvement Program).…”
mentioning
confidence: 71%
“…Additionally, colectomy is used in the elective treatment of SV [5]. In the light of our comprehensive experience, I would like to discuss the data given by Althans et al [1] and some details of the authors' comments.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…I thank Professor Atamanalp for the thoughtful discussion regarding our paper entitled ‘Colectomy for caecal and sigmoid volvulus: a national analysis of outcomes and risk factors for postoperative complications’ . We would like to congratulate him on his cited work of 1026 patients with sigmoid volvulus as this is the largest series in the published literature .…”
mentioning
confidence: 99%